2018
DOI: 10.1177/1078155218788717
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral aspergillosis in a patient on ibrutinib therapy—A predisposition not to overlook

Abstract: Ibrutinib has revolutionized the treatment of B-cell malignancies since its approval for chronic lymphocytic leukemia. It is also used in mantle cell lymphoma, diffuse large B-cell lymphoma, Waldenstrom's macroglobulinemia, among others. It is a Bruton's tyrosine kinase inhibitor that acts on B-cell receptor signaling pathway and predisposes to various infections due to its effects on neutrophils, monocytes and T cells. We present a case of cerebral invasive aspergillosis in a patient being treated with ibruti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…Another retrospective study has shown 37.2% of patients receiving ibrutinib for lymphoid cancer developed invasive fungal infection 9. Multiple case reports also support an association of invasive aspergillosis with ibrutinib therapy,10–14 with several case reports suggesting an association with cryptococcal infection 14–20. Mucormycosis and Pneumocystis jirovecii with ibrutinib therapy have also been described 21–23…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Another retrospective study has shown 37.2% of patients receiving ibrutinib for lymphoid cancer developed invasive fungal infection 9. Multiple case reports also support an association of invasive aspergillosis with ibrutinib therapy,10–14 with several case reports suggesting an association with cryptococcal infection 14–20. Mucormycosis and Pneumocystis jirovecii with ibrutinib therapy have also been described 21–23…”
Section: Discussionmentioning
confidence: 98%
“…More indolent forms of PA are associated with chronic lung disease and milder immunodeficiencies. Here we describe three cases of PA developing in patients receiving TKI treatment, an association that has only recently been reported with ibrutinib 8–14…”
Section: Introductionmentioning
confidence: 86%
“…The number of case reports of opportunistic fungal infections associated with BTK inhibitor use is increasing [3][4][5][6]. Those reports are indicating unusual locations of invasive fungal infections such as extrapulmonary Pneumocystis jirovecii, disseminated Cryptococcus neoformans, and CNS Aspergillus [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although data suggest better tolerability of BTK inhibitors as compared to CIT, infections are still reported with the use of BTK inhibitors. There are several case reports of invasive fungal infections linked to the use of BTK inhibitors [3][4][5][6]. For example, a series of 33 cases of invasive fungal infections in patients receiving ibrutinib alone or in combination have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the commonest reported fungi were Candida, followed by P. jirovecii and Cryptococcus. In the RCTs and LTE studies, no cases of endemic mycotic infections (histoplasmosis, coccidioidomycosis and blastomycosis) were observed, but Candida albicans (n = 3) C. glabrata (n = 1) C. parapsilosis (n = 1) C. [11,77,78], pulmonary (n = 1) [79], myocardial (n = 1) [80], cryptococcosis disseminated (n = 2) [81,82], CNS (n = 4) [20,83,84], pneumonia (n = 1) [83], empyema (n = 2) [19,85], Candida pneumonia (n = 2) [86,87], mucormycosis invasive (n = 1) [86], abdominal (n = 1) [84], sinus (n = 1) [88] skin (n = 2) [89,90], PJP (n = 5) [25] Acalabrutinib (Calquence) PJP Pneumocystis jirovecii pneumonia; PCM paracoccidioidomycosis *Single centre retrospective analysis. #Meta-analysis of everolimus and temsirolimus randomised controlled trials presumably few patients were enrolled from regions where these organisms are endemic [45].…”
Section: Janus Kinase/signal Transducers and Activators Of Transcriptmentioning
confidence: 98%